A Multi-Computer System With a Flexible Tool for Efficient Traffic Management - Baričević, Hrvoje; Kraš, Antun (Promet - Traffic&Transportation, 2012)
In recent years, several computer models have been developedto help traffic engineers understand and solve traffic problems.Although traffic enginee1ing studies continue to be carriedout by manual methods, computer approaches are beingincreasingly employed for traffic engineering analyses and design.Many authors have described the most common computerprograms for signa/timing optimization and traffic simulationflows.The volume of traffic is increasing all the time. It is happeningso fast that the space available for new roads and car parkscannot grow apace enough. That would mean too great a strainon humans and the environment. This paper describes amulti-computer system VRS 2100 with an integral part of collectivetraffic management.